2020
DOI: 10.3389/fonc.2020.01091
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Stem Cell Subpopulations Are Present Within Metastatic Head and Neck Cutaneous Squamous Cell Carcinoma

Abstract: Cancer stem cells (CSCs) have been identified in many cancer types including primary head and neck cutaneous squamous cell carcinoma (HNcSCC). This study aimed to identify and characterize CSCs in metastatic HNcSCC (mHNcSCC). Immunohistochemical staining performed on mHNcSCC samples from 15 patients demonstrated expression of the induced pluripotent stem cell (iPSC) markers OCT4, SOX2, NANOG, KLF4, and c-MYC in all 15 samples. In situ hybridization and RT-qPCR performed on four of these mHNcSCC tissue samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 70 publications
0
24
0
Order By: Relevance
“…There is increasing evidence of the role of the RAS in tumorigenesis, and metastasis [ 23 , 24 , 57 ]. We have recently demonstrated the presence of CSC subpopulations that express the ESC markers OCT4, NANOG, SOX2, KLF4, and c-MYC in primary HNcSCC [ 19 ] and mHNcSCC [ 20 ]. In this study we have shown expression of five components of the RAS: angiotensinogen, PRR, ACE, AT 1 R, and AT 2 R, in mHNcSCC tissue samples.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There is increasing evidence of the role of the RAS in tumorigenesis, and metastasis [ 23 , 24 , 57 ]. We have recently demonstrated the presence of CSC subpopulations that express the ESC markers OCT4, NANOG, SOX2, KLF4, and c-MYC in primary HNcSCC [ 19 ] and mHNcSCC [ 20 ]. In this study we have shown expression of five components of the RAS: angiotensinogen, PRR, ACE, AT 1 R, and AT 2 R, in mHNcSCC tissue samples.…”
Section: Discussionmentioning
confidence: 99%
“…mHNcSCC tissue samples from 20 patients aged 51–87 (mean, 77.7) years ( Table S1 ), including those used in our previous study [ 20 ], were sourced from the Gillies McIndoe Research Institute Tissue Bank. This study was approved by the Central Regional Health and Disability Ethics Committee (Ref.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is made available under a preprint (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in The copyright holder for this this version posted December 7, 2020. ; https://doi.org/10.1101/2020.12.07.414599 doi: bioRxiv preprint 13 2006; Wei et al, 2019). Although the underlying molecular mechanisms remain to be defined, CSC plasticity and heterogeneity could induce tumor progression and resistance to therapy (Das et al, 2020;Kilmister et al, 2020;Martin-Castillo et al, 2013;Thankamony et al, 2020). For example, intratumoral heterogeneity is a major ongoing challenge for effective cancer therapy, while CSCs are responsible for intratumoral heterogeneity, therapeutic resistance, and metastasis, which may be because cancer cells exhibit a high level of plasticity and an ability to dynamically switch between CSC and non-CSC states or among different subsets of CSCs (Thankamony et al, 2020).…”
Section: Discussionmentioning
confidence: 99%